Therapies to Increase ApoA-I and HDL-Cholesterol Levels - William M. Brown; Fabrizio S. Chiacchia (AboutScience Srl, 2008)
Cholesterol is transported around the body in the form of lipoprotein (lipid/protein) complexes, because it is almost insoluble in water. High-density lipoprotein (HDL) particles transport cholesterol from tissues back to the liver for excretion. Epidemiological studies have shown an inverse relationship between blood levels of HDL-cholesterol (HDL-c) and the incidence of clinically signiﬁcant atherosclerosis. The beneﬁcial effects of HDL in altering atherosclerotic disease are believed to involve elevated levels of HDL enhancing the efﬂux of cholesterol from arterial walls, increasing transport of cholesterol from arteries to the liver for excretion. This reverse cholesterol transport (RCT) pathway is used to explain both HDL's role in lipid metabolism and the inverse association between HDL-c plasma concentration and the risk of car- diovascular disease. Based on the RCT model, ApoA-I is an attractive target for therapeutic intervention. Experimental manipulations to increase production of ApoA-I have been associated with reduced atherogenicity. There is a continuing need for novel therapies that increase the biosynthesis of HDL, to inhibit the progression of and even bring about regression of atherosclerosis. Small molecule compounds that increase the production of endogenous ApoA-I would be attractive therapeutic agents for treating dyslipidemias.